Progress in Clinical Research on Gonadotropin-Releasing Hormone Receptor Antagonists for the Treatment of Prostate Cancer - Liu YF; Fu SQ; Yan YC; Gong BB; Xie WJ; Yang XR; Sun T; Ma M (Dove Medical Press, 2021)
Yi-Fu Liu, Sheng-Qiang Fu, Yu-Chang Yan, Bin-Bin Gong, Wen-Jie Xie, Xiao-Rong Yang, Ting Sun, Ming Ma Department of Urology, The First Affiliated Hospital of Nanchang University, Nanchang, 330000, Jiangxi Province, People’s Republic of ChinaCorrespondence: Ming MaDepartment of Urology, The First Affiliated Hospital of Nanchang University, Nanchang, 330000, Jiangxi Province, People’s Republic of ChinaEmail mm15070835359@163.comAbstract: Gonadotropin-releasing hormone (GnRH) receptor agonists are still the most commonly used androgen deprivation treatment (ADT) drugs for prostate cancer in clinical practice. Currently, the GnRH receptor antagonists used for endocrine therapy for prostate cancer primarily include degarelix and relugolix (TAK-385). The former is administered by subcutaneous injection, while the latter is an oral drug. Compared to GnRH agonists, GnRH antagonists reduce serum testosterone levels more rapidly without an initial testosterone surge or subsequent microsurges. This review focuses on the mechanism of action of GnRH antagonists and agonists, the developmental history of GnRH antagonists, and emerging data from clinical studies of the two antagonists used as endocrine therapy for prostate cancer.Keywords: gonadotropin-releasing hormone, prostate cancer, degarelix, relugolix